Effect of Different Ratios of Chicken Meat to Fresh Osyter Mushroom (Pleurotus sajor-caju) on the Physicochemical Properties and Sensory Acceptability of Sausages - Faridah Yahya; Hun Tze Ting (Food, Agriculture and Natural Resources - NETWORKS, 2020)
This study was aimed to determine the effect of different ratios of chicken meat to fresh oyster mushroom (Pleurotus sajor-caju) on the physicochemical properties and sensory acceptability of chicken sausages. Five formulations of sausages were prepared by different combinations of chicken meat with fresh oyster mushroom (100:0, 85: 15, 70: 30, 55: 45 and 40: 60). The physicochemical analyses included color profile, texture profile, calorie values, and proximate analysis were carried in triplicate while sensory acceptability of chicken sausages were evaluated using sensory acceptance test with 7-point of hedonic scale. Results indicated that the b* value as well as the hardness, springiness, cohesiveness, gumminess, and chewiness of sausages were significantly (p